2012
DOI: 10.1016/j.atherosclerosis.2012.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness and calcification in men in a population-based international study

Abstract: Objectives Aortic stiffness, a hallmark of vascular aging, is an independent risk factor of cardiovascular disease and all-cause mortality. The association of aortic stiffness with aortic calcification in middle-aged general population remains unknown although studies in patients with end-stage renal disease or elderly subjects suggest that aortic calcification is an important determinant of aortic stiffness. The goal of this study was to examine the association of aortic calcification and stiffness in multi-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 30 publications
2
56
1
Order By: Relevance
“…Age‐associated enlargement of AoD is thought to be associated with tissue remodeling of the aortic wall that includes a reduction in elastin fiber, increased collagen deposition, and increased calcification 2, 7. These structural alterations are associated with increased aortic stiffness 2, 7, 21. Thus, we speculate that the resultant functional changes of the aorta might contribute to the relationship between AoD and cardiovascular events observed in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Age‐associated enlargement of AoD is thought to be associated with tissue remodeling of the aortic wall that includes a reduction in elastin fiber, increased collagen deposition, and increased calcification 2, 7. These structural alterations are associated with increased aortic stiffness 2, 7, 21. Thus, we speculate that the resultant functional changes of the aorta might contribute to the relationship between AoD and cardiovascular events observed in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Of note, several studies have recently reported that calcification of the aorta is associated positively with arterial stiffening both in hemodialysis patients [37,38] and in other cohorts [39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the relation between arterial stiffness and aortic or coronary calcifications. [14][15][16] However, the relationship between arterial stiffness and carotid plaque components, either calcification or vulnerable plaque components, has received less attention. By examining the roll of vascular wall properties in the context of atherosclerosis formation, we…”
mentioning
confidence: 99%